Simulation of microwave propagation properties in human abdominal tissues on wireless capsule endoscopy by FDTD. (March 2019) - Hao, Jiong-Ju; Lv, Liang-Jun; Ju, Lu; Xie, Xun; Liu, Yu-Jie; Yang, Hong-Wei
Highlights: In this paper, a model of the application of wireless capsule endoscope in human abdomen is proposed. The propagation of the microwave in human abdominal tissues at four frequencies, such as 50 MHz, 300 MHz, 700 MHz and 900 MHz, is numerically analyzed by using two-dimensional FDTD method. The results show that the large electrical impedance mismatches between the tissue layers result in reflection of microwaves from the interface of layers. The interference of reflected waves is related to the effective conductivity of the tissue and the number of layers of biological tissues the microwave passes through. The interference of reflected waves is positively correlated with the effective conductivity of human tissue, and negatively correlated with the number of layers of human tissue which microwaves pass through. Abstract: The wireless capsule endoscopy plays an important role in the treatment and detection of gastrointestinal diseases. It is of great significance to research the interaction between microwaves and human abdominal tissues during application of wireless capsule endoscope. In this paper, a model of the application of wireless capsule endoscope in human abdomen is proposed. The propagation of the microwaves in human abdominal tissues at four frequencies, such as 50MHz, 300MHz, 700MHz and 900MHz, is numerically analyzed by 2D-FDTD method. The results show that the large electrical impedance mismatches between the tissue layers result in reflection of microwaves from the interface of layers. The interference of reflected waves is related to the effective conductivity of the tissues and the number of layers of biological tissue which microwave pass through. The interference of reflected waves is positively correlated with the effective conductivity of human tissue, and negatively correlated with the number of layers of human tissue the microwaves pass through. The effect of the dielectric constant in the human tissues on both the distribution of electric field and the phase is higher than that of the effective conductivity. The changes of the effective conductivity in human tissue lead to sharply changes in the SAR, and the changes of the distribution of the electric field cause smoothly changes in the SAR of human tissues. Therefore, in the application of wireless capsule endoscopy for pathological examination, the antenna should be prevented from being wrapped by closed tissues with high dielectric constant as much as possible. When microwave is used to transmit the signals, it is necessary to reduce the number of layers and thickness of biological tissues the microwaves pass through. Effective conductivity should be given priority in assessment the safety of electromagnetic by calculating the specific absorption rate of human tissues.